Evaluation of a Methylcellulose and Hyaluronic Acid Hydrogel as a Vehicle for Rectal Delivery of Biologics - Andreea Aprodu; Julia Mantaj; Bahijja Raimi-Abraham; Driton Vllasaliu (MDPI AG, 2019)
Biologics have changed the management of Inflammatory Bowel Disease (IBD), but there are concerns regarding unexpected systemic toxicity and loss of therapeutic response following administration by injection. Local delivery of biologics directly to the inflamed mucosa via rectal enema administration addresses the problems associated with systemic administration. Hydrogels are potentially useful delivery vehicles enabling rectal administration of biologics. Here, we prepared a hydrogel system based on methylcellulose (MC) and hyaluronic acid (HA), which possesses mucosal healing properties, incorporating a model macromolecular drug, namely (fluorescently-labeled) bovine serum albumin (BSA). The BSA-loaded MCHA hydrogel showed temperature-dependent gelation (liquid-like at 20 °C and gel-like at 37 °C) and shear thinning behavior, with these being important and desirable characteristics for rectal application (enabling easy application and retention). BSA release from the MCHA system at 37 °C was linear, with 50% of the loaded drug released within 2 h. The system demonstrated acceptable toxicity towards intestinal (colon) Caco-2 epithelial cells, even at high concentrations. Importantly, application of the BSA-loaded MCHA hydrogel to polarized Caco-2 monolayers, with or without an exemplar absorption enhancer, resulted in transintestinal permeability of BSA. The study therefore indicates that the MCHA hydrogel shows potential for topical (rectal) delivery of biologics in IBD.